Wakaf Literation to Appear An Interference in Mentify for Milenial: Implementation for Students in Madrasah Aliyah State 4 Bantul - Saputri, Eva Nopalasari; Latifah, Halim Pandu; Almunawir, Al Virizky Arjunitha; Fuadi, Fahmi Hasan; Nisa, Ayu Himatun; Akbar, Maulana Ali; Setiawan, Alfan Rois; Safitri, Afirsta Dyah Mega; Pratiwi, Inayah Nadhira; Saripudin, Ajis; Rizqi, Anis Fathul (FEBI UIN Sunan Kalijaga Yogyakarta, 2020)
Community service is carried out by conducting endowment socialization for high school / MA students in order to foster social awareness through endowments, bearing in mind that the community's understanding of endowment is only synonymous with parents and those who have wealth. Through waqf literacy with waqf tests strategies aimed at assessing students' understanding of waqf, fostering interest in waqf among students or the community itself, creating students and communities who are socially aware through waqf. This method of socialization uses the method of direct teaching patterns, questions and answers, and assignments or tests. The socialization participants consisted of 33 students from class XI IPS MAN 4 Bantul. The total number of pre-test and post-test questions is 10 questions that are true or false. Where each question has 10 points. From the results of the pre-test evaluation, an average value of 59.39 was obtained with a vulnerable value of 30-70 and the results of the post-test evaluation obtained an average value of 81.21 with a vulnerable value of 70-100. The results of the overall evaluation there was a significant increase in value of 21.82, the results showed the method was considered quite useful in terms of grades and enthusiasm of the students. Apart from that, there are a number of questions that show that students are truly enthusiastic about endowments.Keywords: waqf literacy, readability, waqf